PENGEMBANGAN MODEL KONSELING BERBASIS NEUROSAINS TEKNIK VISUAL IMAGERY UNTUK MENINGKATKAN KONSENTRASI BELAJAR SISWA SMP - Ni Kadek Anggi Damayanthi; Kadek Suranata; Kadek Ari Dwiarwati (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT Learning concentration is a fundamental prerequisite for successful learning; however, many junior high school students still experience difficulty maintaining attention throughout classroom activities. This condition highlights the need for guidance and counseling services that are not only preventive in nature but also grounded in an understanding of how the brain processes and sustains attention. In response to this need, the present study developed a neuroscience-based counseling guide incorporating the visual imagery technique as a strategy to enhance students’ learning concentration. The study employed the Research and Development (R&D) approach using the Borg and Gall model, integrated with a Single Subject Design (SSD) employing an A–B–A design. The development process involved needs assessment, planning, product development, expert validation, revision, and limited field testing involving three students from SMP Negeri 1 Sukasada. Data were collected through questionnaires, observations, and documentation, and were analyzed using the Content Validity Ratio (CVR), Content Validity Index (CVI), descriptive analysis, and the Wilcoxon test. The findings demonstrated that the developed counseling guide possessed very high validity, was highly practical for implementation, and effectively improved students’ learning concentration. The primary contribution of this study lies in integrating neuroscience principles with the visual imagery technique into a structured school counseling guide, offering an innovative evidence-based alternative for school counselors to deliver more systematic, scientifically grounded, and effective counseling services aimed at improving students’ learning concentration. ABSTRAK Konsentrasi belajar merupakan prasyarat penting bagi keberhasilan proses pembelajaran, namun masih banyak siswa sekolah menengah pertama yang mengalami kesulitan mempertahankan fokus selama kegiatan belajar. Kondisi ini menuntut tersedianya layanan bimbingan dan konseling yang tidak hanya bersifat preventif, tetapi juga didasarkan pada pemahaman mengenai cara kerja otak dalam mengoptimalkan perhatian. Berangkat dari kebutuhan tersebut, penelitian ini menghasilkan sebuah panduan konseling berbasis neurosains yang memanfaatkan teknik visual imagery sebagai strategi untuk meningkatkan konsentrasi belajar siswa SMP. Pengembangan produk dilakukan melalui pendekatan Research and Development model Borg and Gall yang dipadukan dengan desain Single Subject Design (SSD) pola A-B-A. Proses penelitian mencakup analisis kebutuhan, perancangan, pengembangan, validasi, revisi, dan uji coba terbatas pada tiga siswa SMP Negeri 1 Sukasada. Data diperoleh melalui angket, observasi, dan dokumentasi, kemudian dianalisis menggunakan Content Validity Ratio (CVR), Content Validity Index (CVI), analisis deskriptif, serta uji Wilcoxon. Hasil penelitian memperlihatkan bahwa panduan yang dikembangkan memiliki tingkat validitas yang sangat tinggi, praktis untuk diterapkan, dan efektif meningkatkan konsentrasi belajar siswa. Kontribusi utama penelitian ini terletak pada pengintegrasian prinsip neurosains dengan teknik visual imagery ke dalam sebuah panduan konseling yang memberikan alternatif inovatif bagi guru bimbingan dan konseling dalam menyelenggarakan layanan yang lebih ilmiah, terstruktur, dan berorientasi pada peningkatan kualitas belajar siswa.